2019
DOI: 10.1016/j.cancergen.2019.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of genetic testing for germline BRCA1/2 pathogenic variants in a predominantly Hispanic population

Abstract: Background-Genetic counseling is under-utilized in women who meet family history criteria for BRCA1 and BRCA2 (BRCA1/2) testing, particularly among racial/ethnic minorities. We evaluated the uptake of BRCA1/2 genetic testing among women presenting for screening mammography in a predominantly Hispanic, low-income population of Washington Heights in New York City. Methods-We administered the Six-Point Scale (SPS) to women presenting for screening mammography at Columbia University Irving Medical Center (CUIMC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A conducive study of 369 Hispanic women eligible for testing due to family history of breast/ovarian cancers, only 4.6% had reported being referred to prior BRCA1/2 testing [46]. Past literature has highlighted ethnic differences regarding the pathological characteristics of BRCA1/2-associated breast cancers [47], physician-patient communication during and after genetic testing [48], and epidemiological trends among Hispanic women in BRCA1/2 testing [49], showing that this group has a more di cult time nding and communicating care [41].…”
Section: Discussionmentioning
confidence: 99%
“…A conducive study of 369 Hispanic women eligible for testing due to family history of breast/ovarian cancers, only 4.6% had reported being referred to prior BRCA1/2 testing [46]. Past literature has highlighted ethnic differences regarding the pathological characteristics of BRCA1/2-associated breast cancers [47], physician-patient communication during and after genetic testing [48], and epidemiological trends among Hispanic women in BRCA1/2 testing [49], showing that this group has a more di cult time nding and communicating care [41].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, with the start of traditional Medicaid expansion, New York State issued criteria for coverage of BRCA testing in Medicaid recipients [ 52 ]. Despite the revision, a study of 3055 predominantly low-income Latina women who had undergone screening mammography between 2014 and 2016 at a Columbia University medical center in Washington Heights, New York City revealed persistent underutilization [ 53 ]. Twelve percent of the women met family history criteria for BRCA1/2 testing, yet <5% had previously undergone testing.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Another study demonstrated that while 12% of women from a predominantly Hispanic population met criteria for BRCA1/2 testing, less than 5% reported receiving this testing. 32 This suggests additional barriers exist and that there is a need to further evaluate systematic and patient barriers beyond physician education. System-related barriers may include access to resources, trained staff, up-to-date materials, costs for community-based genetic testing, and timely communication from referrals.…”
Section: Discussionmentioning
confidence: 99%